CREATING A HEALING ENVIRONMENT: BEHAVIORAL ARCHITECTURE AT SIBOLANGIT DRUG REHABILITATION CENTER - Purba, Anastasya Putri; Bahri , Samsul (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The issue of drug abuse is a global concern with a significant prevalence in Indonesia. Therefore, designing a Drug Rehabilitation Center is essential to provide mental and spiritual healing for victims of substance abuse. A drug rehabilitation center is a crucial facility to support the recovery and rehabilitation of individuals trapped in drug abuse. The application of a behavioral architecture approach is highly relevant to creating an environment that effectively supports the rehabilitation process. This study examines the architectural design of the drug rehabilitation center in Sibolangit, North Sumatra, with a focus on integrating the principles of behavioral architecture. The main objective of this research is to design a space that not only meets physical needs but also facilitates positive behavioral changes in the residents.